Volterra Integral Equations via Triangular and Hybrid Orthogonal Functions - Mukhopadhyay, Anirban; Ganguly, Anindita; Chatterjee, Saumya Deep (International Journal of Computer Sciences and Engineering, 2025)
We have expounded a new simple algorithm to solve non-linear Volterra integral equations via HF and drawn a comparative study between HF and TF in solving two classes of Volterra integral equations, i.e. Volterra integral equation of 2nd kind and Volterra-Hammerstein equation. To exemplify the usability of this algorithm we have dealt an optimal control problem of a deterministic system via this algorithm.